Incidence and Effects of Acquisition of the Phage-Encoded ssa Superantigen Gene in Invasive Group A Streptococcus - Chiang-Ni, Chuan; Liu, Yen-Shan; Lin, Chieh-Yu; Hsu, Chih-Yun; Shi, Yong-An; Chen, Yi-Ywan M.; Lai, Chih-Ho; Chiu, Cheng-Hsun (Frontiers in Microbiology, 2021)
The acquisition of the phage-encoded superantigen ssa by scarlet fever-associated group A Streptococcus (Streptococcus pyogenes, GAS) is found in North Asia. Nonetheless, the impact of acquiring ssa by GAS in invasive infections is unclear. This study initially analyzed the prevalence of ssa+ GAS among isolates from sterile tissues and blood. Among 220 isolates in northern Taiwan, the prevalence of ssa+ isolates increased from 1.5% in 2008–2010 to 40% in 2017–2019. Spontaneous mutations in covR/covS, which result in the functional loss of capacity to phosphorylate CovR, are frequently recovered from GAS invasive infection cases. Consistent with this, Phostag western blot results indicated that among the invasive infection isolates studied, 10% of the ssa+ isolates lacked detectable phosphorylated CovR. Transcription of ssa is upregulated in the covS mutant. Furthermore, in emm1 and emm12 covS mutants, ssa deletion significantly reduced their capacity to grow in human whole blood. Finally, this study showed that the ssa gene could be transferred from emm12-type isolates to the emm1-type wild-type strain and covS mutants through phage infection and lysogenic conversion. As the prevalence of ssa+ isolates increased significantly, the role of streptococcal superantigen in GAS pathogenesis, particularly in invasive covR/covS mutants, should be further analyzed.